Infrastructure Assessment for Developing Route Evacuation of Bengawan Solo River Flood at Bojonegoro District - Zharin F. Syahdinar; Umboro Lasminto (IPTEK Journal of Proceedings Series, 2017)
Bengawan Solo River is the biggest watersheet in java, Indonesia. It is reach between two provinces, Central Java and East Java. The flood’s happens almost every year on this river. The floods caused by increased rainfall on rainy season, and land use in upstream has changed too. The community not want to abandon their land so, they must living and adaptable with disaster. Beside that, decrease of river’s flow capacity and catchment area are the significant factor of causing floods in Bengawan Solo river. The villages nearest with river get susceptible floods area. In Bojonegoro district there was 23 of flooded sub-district. Using supported information and map of road network, topography, provisional care, and infrastructure condition. Then assessment of infrastructure damaged such as roads, bridges, railway, etc. from that information and assessment, capable to created evacuated lines map for flood’s victim in Bojonegoro district using GIS. This map can useful as a guide the victim to safety line and nearest provisional care when flood disaster has come out.